PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN HASIL BELAJAR FISIKA PADA POKOK BAHASAN GEJALA DAN CIRI CIRI GELOMBANG SISWA KELAS XII SMAN 9 PEKANBARU - Gustariani Gustariani (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is motivated by the lack of physics student learning outcomes on feature highlights feature of wave class XII SMAN 9 Pekanbaru. This study aims to improve the learning outcomes of physics students on feature highlights wave characteristics class XII SMAN 9 Pekanbaru application of cooperative learning model cooperative integrated reading and composition the subjects were all students of grade XII SMAN 9 Pekanbaru totaling 30 people. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the results of research and discussion can be concluded that the implementation of cooperative learning model cooperative integrated reading and composition (CIRC) in the learning of physics can enhance physical activity and learning outcomes of students on the material characteristics wave traits in class XII SMAN 9 Pekanbaru. it is seen as prior actions of student learning outcomes achieve mastery only 33.3% (10 people) and increased after the first cycle of action reached 53.3% (16 people) and rebounded better in the second cycle, reaching 100% (30 person). These results it can be said that hypothesis was accepted.